2018
DOI: 10.1098/rsif.2018.0174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanistic and statistical methods in forecasting influenza-like illness

Abstract: A variety of mechanistic and statistical methods to forecast seasonal influenza have been proposed and are in use; however, the effects of various data issues and design choices (statistical versus mechanistic methods, for example) on the accuracy of these approaches have not been thoroughly assessed. Here, we compare the accuracy of three forecasting approaches—a mechanistic method, a weighted average of two statistical methods and a super-ensemble of eight statistical and mechanistic models—in predicting sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Accurate forecasting of ILI can support better planning of both pharmaceutical (e.g., vaccines, antivirals and prophylaxis) and non-pharmaceutical (e.g., school closure, social distancing and travel restrictions) interventions against respiratory infections, as well as early preparation for patient surges in healthcare facilities during peak periods of incidence. In recent years, a number of forecasting systems for ILI have been developed [3][4][5][6][7][8][9][10][11][12][13][14], many of which have been applied operationally to forecast ILI in the United States [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate forecasting of ILI can support better planning of both pharmaceutical (e.g., vaccines, antivirals and prophylaxis) and non-pharmaceutical (e.g., school closure, social distancing and travel restrictions) interventions against respiratory infections, as well as early preparation for patient surges in healthcare facilities during peak periods of incidence. In recent years, a number of forecasting systems for ILI have been developed [3][4][5][6][7][8][9][10][11][12][13][14], many of which have been applied operationally to forecast ILI in the United States [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al tested autoregressive nowcasts using several internet data sources and found that they improved 1-week-ahead forecasts [23]. Kandula et al measured the benefit of nowcasting to their flu forecasting model at 8-35% [21]. Finally, our own work shows that a Bayesian seasonal flu forecasting model using ordinary differential equations benefits from filling a one-week reporting delay with internet-based nowcasts [25].…”
Section: Introductionmentioning
confidence: 91%
“…The Existing researches on modeling influenza epidemic falls into two categories: Mechanistic and Statistical models. They are summarized in literature reviews [3][4][5][6] and in the CDC comparisons [7,8]. Researches under statistical category vary according to the different Features and methods used.…”
Section: Introductionmentioning
confidence: 99%